Deciphering natural hazard histories based on tree-ring analyses in contrasting tropical ecosystems of Costa Rica - Quesada Román, Adolfo (2020)
Climatic and anthropogenic changes are contributing to the degradation of different ecosystems in Costa Rica, thereby altering climatic, ecological, and geomorphic conditions. The hypothesis of this PhD thesis is that high tropical biodiversity of Costa Rica and the tropics is suitable to improve the understanding of hydrogeomorphic process dynamics and to generate baseline data on past disasters in a limited-data region. The principal motivation to link natural hazards and dendrochronology in this low-latitude region is the persisting scarcity of data on past hydrogeomorphic processes and the desire to define methods that can reduce its exposure and vulnerability. The principal research aim of this study therefore was to provide reference data that can improve the understanding of hydrogeomorphic processes as well as to explore the potential of tropical tree species in dendrochronological applications. This study thus combines remote sensing, meteorological assessments and tree-ring techniques with statistical analyses, hydraulic modelling, and risk assessments. The innovative nature of this research described the very limited experience available in terms of tree-ring analysis in Costa Rica and the clear lack of understanding on past disasters and their linkage to climate. This study will likely contribute to the implementation of new methodologies in disaster risk research and will hopefully contribute to future adaptation strategies in the tropics, the most biodiverse region of the world.